Exploring the relationship of learning engagement, learning interaction, and learning outcomes in gamified massive open online courses - Yusoff, Azizul Mohd; Salam, Sazilah; Mohamad, Siti Nurul Mahfuzah; Pudjoatmodjo, Bambang (Institute of Advanced Engineering and Science, 2026)
This study investigates the interplay between learning engagement, interaction, and outcomes within the context of gamified massive open online courses (G-MOOCs). By synthesizing literature on MOOCs, gamification, and user engagement, the research identifies significant correlations among these variables. Utilizing a structural equation model partial least squares (SEM-PLS) approach, the study analyzes data from a survey of Bachelor of Computer Science students at a technical and vocational education and training (TVET) public university. Results indicate that both learning engagement and interaction significantly influence learning outcomes, with optimal results achieved when both factors are high. These findings highlight the potential of gamification to enhance educational experiences and suggest directions for future research in gamified learning environments.